Differences in the Quality of Indonesian Language Based on Gender at MI Hudatul Hailalah Bojonegoro (Psycholinguistic Analysis) - Agustin Eka Nuriati; Djatmika Djatmika (Translation and Linguistics (Transling), 2025)
This study uses a psycholinguistic approach to analyze the differences in language quality between male and female students at MI Hudatul Hailalah Bojonegoro. The main focus of this study is the differences in the use of sentence beginnings, sentence structures, and the completeness of the stories produced by each group. The method used is observation and analysis of transcripts of picture stories retold by students. The results of the study indicate that male students tend to use short, direct, and action-focused sentences, while female students are more narrative and detailed and have more complex sentence structures. In addition, the social environment also influences language use, where male students use their mother tongue more often in everyday life, while female students are more exposed to a second language (Indonesian) in their social interactions. This study is expected to provide insight into how gender factors and the social environment shape children's language development.